1992
DOI: 10.1002/pca.2800030605
|View full text |Cite
|
Sign up to set email alerts
|

Structural and conformation analysis of sesquiterpene lactones by proton nuclear magnetic resonance

Abstract: The stereochemistry as well as the conformation of two germacranolides and two 3,4‐epoxyguaianolides were determined by computational methods employing LAOCOON‐III and DAERM programs. The chair‐chair conformation was shown to be preferred by the germacranolide macrocycle in solution, while the A‐ring of 1,10‐dehydro‐3,4‐epoxyguaianolides was shown to be approximately planar. The ten‐membered ring stereochemistry of germacranolides was deduced from the calculated results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…The 1D and 2D NMR data of compound 1 (Table , Figure ), together with the proposed molecular formula and spectroscopic data previously reported in the literature, revealed that it corresponded to a bicyclic sesquiterpenoid with a germacrane-type skeleton with a 6,7- trans -fused lactone ring, and it was identified as tomenphantin A. , The relative stereochemistry was assigned according to previous data and from a NOESY experiment (Figure and Table S1, Supporting Information) and matched those previously described for similar germacranolides . The coupling constants J 8β–9α = 11.2 Hz and J 8β–9β = 1.7 Hz were consistent with the ester side chain at C-8 being in an α-orientation, , while the signal for H-6 as a doublet of doublets at δ H 4.30 and J 5α,6β = 9.2 Hz and J 6β,7α = 6.6 Hz indicated a trans -axial relationship between H-5α, H-6β, and H-7α, assuming that the latter is in an α-orientation, as in all the known germacranolides obtained from plants . NOESY correlations of H-1/H-5α, H-7α suggested that these protons are cofacial and were observed as well between H6β and Me-15 (Figure and Table S1, Supporting Information) .…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…The 1D and 2D NMR data of compound 1 (Table , Figure ), together with the proposed molecular formula and spectroscopic data previously reported in the literature, revealed that it corresponded to a bicyclic sesquiterpenoid with a germacrane-type skeleton with a 6,7- trans -fused lactone ring, and it was identified as tomenphantin A. , The relative stereochemistry was assigned according to previous data and from a NOESY experiment (Figure and Table S1, Supporting Information) and matched those previously described for similar germacranolides . The coupling constants J 8β–9α = 11.2 Hz and J 8β–9β = 1.7 Hz were consistent with the ester side chain at C-8 being in an α-orientation, , while the signal for H-6 as a doublet of doublets at δ H 4.30 and J 5α,6β = 9.2 Hz and J 6β,7α = 6.6 Hz indicated a trans -axial relationship between H-5α, H-6β, and H-7α, assuming that the latter is in an α-orientation, as in all the known germacranolides obtained from plants . NOESY correlations of H-1/H-5α, H-7α suggested that these protons are cofacial and were observed as well between H6β and Me-15 (Figure and Table S1, Supporting Information) .…”
Section: Resultssupporting
confidence: 80%
“…This compound yielded very similar spectroscopic data to compound 1 , and, in light of the probable same biogenetic origin, the same relative configuration was assigned. The α-orientation of the C-8 side chain as in compound 1 was confirmed by the coupling constants observed for H-8 ( J 8β,9α = 9.2 Hz and J 8β,9β = 1.2 Hz). , The trans -axial orientation of Hα-5, Hβ-6 and Hα-7 was supported by the coupling constants observed for H-6 ( J 5α,6β = 9.9 Hz and J 6β,7α = 6.7 Hz) . NOESY correlations of CH 3 -15 with both H-14 (δ H 3.89, 4.05) and H-6β (δ H 4.97) and also from H7α (δ H 3.24) to H-1 (δ H 5.11) and H-5α (δ H 4.93) confirmed the orientation assigned to H-5, -6, -7, and -8 (Figure and Table S1, Supporting Information).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In cyclic systems, conformational averaging may have its origins in inversion of the ring, for example, the interconversion between different chair forms, termed a ring flip, or between chair and boat forms. In cases such as cycloheptane or cyclohexane, the energy barrier has been calculated to be between 7 and 10 kcal mol –1 . Conformational averaging is also commonly encountered in fused ring systems including perhydroazulenes , and guaianolide sesquiterpenes, , where activation barriers are typically >10 kcal mol –1 . A second form of conformational averaging is restricted rotation.…”
mentioning
confidence: 99%